BEYOND STANDARD CARE: CURCUMIN AS COMBINATION THERAPY IN INFLAMMATORY BOWEL DISEASE: A SYSTEMATIC REVIEW (Journal of Medical & Health Sciences Review, 2025)
Background: Inflammatory Bowel Disease (IBD), comprising ulcerative colitis (UC) and Crohn’s disease (CD), is a chronic gastrointestinal disorder marked by inflammation. Curcumin, derived from turmeric, is known for its anti-inflammatory properties. This systematic review aims to assess the efficacy and safety of curcumin as adjunct therapy in IBD treatment.Methods: A comprehensive search across multiple databases (PubMed, Embase, Cochrane Library, Scopus, Web of Science, CNKI, and ClinicalTrials.gov) was conducted up to April 2025 using search string was used: ("Curcumin"[Mesh] OR curcumin[tiab]) AND ("Inflammatory Bowel Diseases"[Mesh] OR "inflammatory bowel disease"[tiab] OR IBD[tiab] OR "ulcerative colitis"[tiab] OR "Crohn's disease"[tiab]) AND ("Drug Therapy, Combination"[Mesh] OR "combination therapy"[tiab] OR "adjunct therapy"[tiab] OR "combined treatment"[tiab]). Randomized controlled trials (RCTs) assessing curcumin in combination with standard IBD treatments were included. Data were extracted and quality assessment was done through RoB2.Results:  In this systematic review of 13 randomized controlled trials involving 1,150 participants, curcumin was administered orally or rectally as an adjunct to standard therapies. It demonstrated a consistent benefit in patients with inflammatory bowel disease specifically targeting ulcerative colitis. Ten studies reported significantly higher rates of clinical remission in curcumin-treated groups, while eight showed endoscopic improvement, particularly with advanced or rectal formulations. Improvements in quality of life were noted in four trials, though evidence remained limited. Across all studies, curcumin was well tolerated, with no significant increase in adverse events compared to controls. Only one pilot study addressed Crohn’s disease, indicating possible benefit but with very low certainty. Overall, curcumin appears effective and safe as an adjunct therapy in mild-to-moderate UC, with moderate-certainty evidence supporting its role in clinical remission and mucosal healing.Conclusion: Curcumin appears to improve treatment outcomes in inflammatory bowel disease specifically ulcerative colitis when used alongside standard therapy, without increasing adverse effects. Future high-quality RCTs are necessary to further evaluate curcumin's potential in its treatment.